2000
DOI: 10.1016/s0002-9440(10)64765-7
|View full text |Cite
|
Sign up to set email alerts
|

Liver Regeneration in Rats with Retrorsine-Induced Hepatocellular Injury Proceeds through a Novel Cellular Response

Abstract: The adult rodent liver contains at least two recognized populations of cells with stem-like properties that contribute to liver repair/regeneration under different pathophysiological circumstances: (i) unipotential committed progenitor cells (differentiated hepatocytes and biliary epithelial cells) and (ii) multipotential nonparenchymal progenitor cells (oval cells). In retrorsine-induced hepatocellular injury the capacity of fully differentiated rat hepatocytes to replicate is severely impaired and massive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
205
4
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(220 citation statements)
references
References 35 publications
8
205
4
3
Order By: Relevance
“…This figure might be even higher if not all the cells that migrated to the liver actually took part in repopulation, and the authors suggested that there might be a sub-population of hepatocyte stem cells designated as 'regenerative transplantable hepatocytes' (RTHs). We could speculate that perhaps these RTHs are analogous to the small hepatocyte-like progenitors (SHPCs) described by Gordon [22]? If rats are pretreated with retrorsine, a pyrrolizidine alkaloid metabolized by the hepatocyte's cytochrome P450 system to metabolites that form DNA adducts, then after a two-thirds PH, regeneration is accomplished by the activation, expansion and differentiation of these so-called SHPCs.…”
Section: Hepatocytesmentioning
confidence: 83%
“…This figure might be even higher if not all the cells that migrated to the liver actually took part in repopulation, and the authors suggested that there might be a sub-population of hepatocyte stem cells designated as 'regenerative transplantable hepatocytes' (RTHs). We could speculate that perhaps these RTHs are analogous to the small hepatocyte-like progenitors (SHPCs) described by Gordon [22]? If rats are pretreated with retrorsine, a pyrrolizidine alkaloid metabolized by the hepatocyte's cytochrome P450 system to metabolites that form DNA adducts, then after a two-thirds PH, regeneration is accomplished by the activation, expansion and differentiation of these so-called SHPCs.…”
Section: Hepatocytesmentioning
confidence: 83%
“…When rats are treated with retrorsine, this compound is metabolized by the hepatocyte's cytochrome P450 (CYP) mixed function oxidase system to a compound that forms DNA adducts, blocking the cell's ability to proliferate; then, the response to PH regeneration is activation, expansion and differentiation of so-called 'small hepatocyte-like' progenitors (SHPCs) [107]. These cell clusters lack CYP enzymes that are usually readily induced by retrorsine, and this probably accounts for their resistance to the anti-proliferative effects of retrorsine.…”
Section: Digestive Tractmentioning
confidence: 99%
“…Stem cells capable of reconstituting the tissues in which they reside include myosatellite cells in skeletal muscle (Grounds, 1999), chondroblasts in the perichondrium surrounding cartilage (Yotsuyanagi et al, 1999), oval cells in the liver (Gordon et al, 2000), preductal stem cells in the pancreas (Bonner-Wier et al, 2000;Ramiya et al, 2000), basal stem cells of epithelial tissues (Slack, 2000), and neuronal stem cells in the brain (Gage, 2000). By contrast, other studies have shown that stem cells residing in one tissue can differentiate into cell types of another tissue.…”
mentioning
confidence: 99%